22 CX3CR1+ MONONUCLEAR PHAGOCYTES CONTROL IMMUNITY TO INTESTINAL FUNGI. (7th February 2019) - Leonardi, Irina; Iliev, Iliyan; Li, Xin; Semon, Alexa
Abstract: Background and Objectives: Recent evidence suggests that intestinal fungal communities possess Immunomodulatory properties and can influence the development of intestinal inflammation. Serum antibodies against the Saccharomyces cerevisiae mannan (ASCA) are a common hallmark of Crohn's Disease (CD) and can develop in response to intestinal fungi. Despite the identification of few molecules involved in the recognition and immunity to intestinal fungi, the cell subsets that initiate and regulate mucosal immune responses to the mycobiota remain unknown. Methods: To assess the role of intestinal CX3CR1 + MNPs in the induction of anti-fungal immune responses, we crossed flox inducible Cx3cr1 DTR mice, with transgenic Cd11c-Cre mice. This strategy allowed for the selective depletion of intestinal CX3CR1 + MNPs upon administration of diphtheria toxin (DT), without affecting CD11b + CD103 + DCs. For the assessment of the antifungal-response at steady state, mice were fed with Candida albicans (1 . 10 8 yeast/mouse) for 10 days. Cx3cr1 DTR or littermate control mice were injected with DT for three consecutive days, prior to the induction of colitis with 3% (w/v) Dextran sulphate sodium (DSS). DT was then administered every second day and DSS water was removed at day 7. To target intestinal fungi, mice were given Fluconazole (0.5 mg/ml, Sigma) in the drinking water for the duration of the DSS treatment, starting 4 days prior the first DSS dose. Results: CX3CR1 + MNPs showed a higher expression of genes involved in fungal recognition (including the fungal C type lectin receptors (CLRs) dectin-1, dectin-2 and mincle by RNA sequencing and quantitative PCR. Confocal microscopy revealed that CX3CR1+ MNPs efficiently recognized Candida in vivo . In the colon and mLN, Candida colonization induced a consistent increase in Th17 cells that was decreased upon depletion of CX3CR1 + MNPs. Further, depletion of CX3CR1 + MNPs led to a significant decrease of antibody production against C. albicans after intestinal colonization and to an overgrowth of C. albicans in the intestines. Genetic depletion of CX3CR1 + MNPs in mice led to changes in gut fungal communities and to severe DSS induced intestinal inflammation that was rescued by antifungal treatment. In CD patients, the missense T280M mutation in the gene encoding CX3CR1 was identified and found to be associated with impaired antifungal responses. Conclusion: Our study show the novel role of CX3CR1 + MNPs as mediators of the interactions between intestinal mycobiota and host immunity during health and disease. Understanding the immunomodulatory properties of fungi and the underlying mechanisms could lead to the implementation of innovative therapeutic strategies for IBD.